The Role of Nursing Advocacy in Indonesia's Border Regions - Fajar Widhi Atmojo (PT Bukuloka Literasi bangsa, 2025)
Nursing advocacy is an important aspect in ensuring the fulfillment of public health rights, especially in border areas that face geographical, social, and cultural challenges. Nurses have a strategic role in protecting patients, empowering communities, and promoting more equitable health policies. This study used a literature review method, analyzing scientific articles, health organization reports, and related research. The analysis was descriptive in nature to describe the forms of nursing advocacy found. The results of the review show that nursing advocacy in border areas includes four main forms: (1) individual advocacy for the protection of patient rights and facilitation of decision-making; (2) community advocacy for community empowerment and increased health literacy; (3) policy advocacy to encourage policies that are responsive to border needs; and (4) social advocacy to address the social determinants of health. Various challenges such as infrastructure limitations, cultural barriers, and lack of policy support affect the effectiveness of advocacy. The role of nurse advocacy is very important in improving the quality of services and health equity in border areas. Strengthening the capacity of nurses, policy support, and cross-sector collaboration are needed so that nursing advocacy can run optimally. Keywords: nursing advocacy, border areas, health equity, the role of nurses, community empowerment.